Modern art and modernism a critical anthology - Frascina, Francis (Routledge, 1987)
Modern Art and Modernism offers firsthand material for the study of issues central to the development of modern art, its theory, and criticism. The history of modern art is not simply a history of works of art, it is also a history of ideas interpretations. The works of critics and theorists have not merely been influential in deciding how modern art is to be seen and understood, they have also influenced the course it has taken. The nature of modern art cannot be understood without some analysis of the concept of Modernism itself.Modern Art and Modernism presents a selection of texts by the major contributors to debate on this subject, from Baudelaire and Zola in the nineteenth century to Greenberg and T. J. Clark in our own times. It offers a balanced section of essays by contributors to the mainstream of Modernist criticism, representative examples of writing on the themes of abstraction and expression in modern art, and a number of important contributions to the discussion of aesthetics and the social role of the artist. Several of these are made available in English translation for the first time, and others are brought together from a wide range of periodicals and specialized collections.This book will provide an invaluable resource for teachers and students of modern art, art history, and aesthetics, as well as for general readers interested in the place of modern art in culture and history.